Baohe pill decoction treats diarrhea induced by high-fat and high-protein diet by regulating lactase-producing bacteria in intestinal mucosa - Zhou, Kang; Yi, Xin; Tan, Zhoujin; Peng, Maijiao; Xiao, Nenqun (Frontiers in Microbiology, 2023)
Introduction This study aimed to investigate the effects of Baohe pill decoction (BPD) on microbial, lactase activity, and lactase-producing bacteria in the intestinal mucosa of mice with diarrhea induced by high-fat and high-protein diet (HFHPD). Methods Thirty male Kunming (KM) mice were randomly divided into normal (NM), model (MD), and BPD groups. Diarrhea models were manufactured using HFHPD combined with a gavage of vegetable oil. At the end of modeling, the BPD group was given BPD (6.63 g·kg−1d−1) intervention twice daily for 3 d. The NM and MD groups were given equal amounts of sterile water. Subsequently, the intestinal mucosa of the mice was collected, one portion was used for microbial and lactase activity measurement, and the other portion was used for its lactase-producing bacterial characteristics by high-throughput sequencing technology. Results Our results showed that microbial and lactase activity of intestinal mucosa decreased significantly following diarrhea in mice (Pmicrobial < 0.05, Plactase < 0.001). After BPD intervention, microbial and lactase activity increased significantly (P < 0.01). The number of operational taxonomic units (OTUs), richness, and diversity index of lactase-producing bacteria increased in the BPD group compared to the MD group (P > 0.05), and the community structure were significant differences (P < 0.01). Compared to other groups, Saccharopolyspora, Rhizobium, Cedecea, and Escherichia were enriched in the BPD group. Notably, the relative abundance of the dominant lactase-producing genus Bifidobacterium decreased after BPD intervention. Discussion The mechanism of BPD in relieving diarrhea induced by HFHPD is closely related to the promotion of lactase activity in the intestinal mucosa, which may be achieved by regulating the structure of lactase-producing bacteria.